2003
DOI: 10.1074/jbc.m302166200
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Different pH Activity Profile in Two Homologous Ketosteroid Isomerases

Abstract: Two homologous ⌬5 -3-ketosteroid isomerases from Comamonas testosteroni (TI-WT) and Pseudomonas putida biotype B (PI-WT) exhibit different pH activity profiles. TI-WT loses activity below pH 5.0 due to the protonation of the conserved catalytic base, Asp-38, while PI-WT does not. Based on the structural analysis of PI-WT, the critical catalytic base, Asp-38, was found to form a hydrogen bond with the indole ring NH of Trp-116, which is homologously replaced with Phe-116 in TI-WT. To investigate the role of Trp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…By analogy with papain and other enzymes (e.g., tyrosyl-tRNA synthetase; ref. 26), a ⌬⌬G T ‡ of Ϸ4 kcal͞mol might be attributed to loss of a hydrogenbonding interaction (27,28) between the Trp-241 side chain and the substrate oxyanion. Trp-241 might similarly stabilize oxyanion intermediate 2 in the deacylation step (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By analogy with papain and other enzymes (e.g., tyrosyl-tRNA synthetase; ref. 26), a ⌬⌬G T ‡ of Ϸ4 kcal͞mol might be attributed to loss of a hydrogenbonding interaction (27,28) between the Trp-241 side chain and the substrate oxyanion. Trp-241 might similarly stabilize oxyanion intermediate 2 in the deacylation step (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 The question is whether the OAH’s function is to serve as a general acid (donating a proton to the intermediate) or as an electrophile (donating hydrogen bonds and stabilizing a charged intermediate). KSI’s capacity to abstract a weakly-acidic α-proton from its steroid substrate (p K a = 12.7 20 ) with its very weak general base (p K a = 3.75 21 ) has previously been attributed to concerted proton transfer, path (ii) in Figure 1B. 18,2225 …”
Section: Introductionmentioning
confidence: 98%
“…Prior functional studies of catalysis by wild-type KSI from P. putida revealed a pK a of approximately 4 that was assigned to the general base, D40 (50). Upon mutation of D40 to Asn, phenolate and equilenin binding studies suggested an enzymatic pK a of approximately 6 that was provisionally assigned to the oxyanion hole residue, D103 (Fig.…”
Section: Pnas Plusmentioning
confidence: 99%